<span>x + (x + 1)
.............
</span>
Answer:
no clue
Step-by-step explanation:
figure it out by yourself
76(1.0825) is 82.27. I hope this helps have a wonderful night!
Answer: s > 5
Step-by-step explanation:
-s² + 25s - 100 > 0
Coefficient of s² is -1, multiply the equation through by -1.
-1 × (-s² + 25s - 100)
s² — 25s + 100
ax² + bx + c
Then you get the factors x and y that gives x + y = b and xy = c
b = -25 and c = 100, x = -20 and y = -5
-20 × -5 = 100 and -20 + -5 = -25
Then
s² — 20s — 5s + 100 > 0
Factorising,
s (s — 20) — 5(s — 20) > 0
(s — 5)(s — 20) > 0
(s — 5) > 0 and (s — 20) > 0
s>5 and s>20
s > 5
Hope this Helps?
Answer:
don't get what
Step-by-step explanation:
..................